Orchestration of the global network organization - Pedersen, Torben (Advances in international management ;, 2014)
The organizational design of the Multinational Corporation (MNC) was a vibrant area of research in the field of International Business and Management during 1970-1990s. However, since then this research has largely faded from our scholarship. The world and environmental forces' have changed substantially in the last decades placing new constraints on MNCs. External shocks have increased and MNCs need to learn how to live with this increased market volatility. Integrating value chains makes MNCs more efficient but also vulnerable. The relentless forces of competition and globalization are forcing MNCs to divide their activities and reach for foreign inputs, markets and partners. By dividing their value chain into discrete pieces' some to be performed in-house, while others are outsourced to partner organizations' MNCs hope to reduce overall costs and risks, while also reaping the benefits of ideas from contractors or alliance partners worldwide. These challenges call for new research on the organizational design of the MNC. It is our intention with this AIM volume to motivate new research on the proper organizational design mechanisms of MNCs as of today.